The Role of Public Relations Management in Bullying Prevention - Novita Saputri; Fathul Fauzi (Al-Qalam Institue, 2025)
Bullying remains a persistent issue in school environments, affecting student well-being and institutional credibility. In response to this challenge, public relations (PR) management plays a crucial role in fostering a safe, inclusive, and communicative school climate. This study aims to examine the role of PR management in bullying prevention at SMP PGRI 9 Sidoarjo by applying core management functions, namely planning, organizing, directing, and controlling. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings reveal that PR serves not only as an information disseminator but also as a program strategist and institutional bridge between internal stakeholders and the community. In the planning stage, PR identifies problems and designs bullying prevention initiatives to strengthen the school’s public image. In the organizing phase, PR coordinates structured teams such as the Violence Prevention and Handling Team (TPPK). Actuating ensures the implementation of activities, including parental engagement and student outreach. Meanwhile, the controlling phase monitors and evaluates program effectiveness. This study contributes to the discourse on educational communication and safety, emphasizing the strategic significance of professional PR management in shaping a trustworthy and responsive school identity.